“PREDESTINASI” SUATU TINJAUAN TEOLOGIS DOKTRIN KESELAMATAN DALAM KAJIAN HERMENEUTIK ROMA 8:29 MENURUTPEMIKIRAN FILSUF AGUSTINUS - Nopi Arsi Bala; Agreis Rumasse, Anna Raswita Putri (Adiba Aisha Amira, 2023)
The purpose of this writing is to find out about predestination as the doctrine of salvation in Romans 8:29 according to the philosopher Augustine's thought as an answer to the question of the doctrine of predestination, on what basis did God determine His choice from the beginning? Because of the problems that arose among Christians regarding the predetermined election of God. If so, what about those whom God did not choose? Then is the election of God the same as the election of humans seen from the criteria? By looking at the existing problems, the writer is interested in studying predestination as one of the doctrines of the Christian faith. The writing method used is a qualitative approach with grammatical-historical methods and literature study methods. The grammar is intended to study the phrase